Holiness, power and growth: The recent history of British Assemblies of God*. Issue 2 (3rd July 2019) - Kay, William K.
ABSTRACT: The paper examines interpretations of holiness within Pentecostalism and specifically British Assemblies of God as (a) personal avoidance of such recreations as going to the cinema or football or cricket matches, reading novels, holding to teetotalism and the like and (b) moral campaigns to clean up the media or nudity in magazines along the lines Mary Whitehouse's activities and it then follows the way the discourse of power from the mid-1990s has diminished or eliminated democratic decision-making and replaced holiness as a master theme among those who pursue an 'apostolic' style of leadership. It will relate these tendencies to growth, or the lack of it, in British Assemblies of God. The original holiness emphasis was activist and partly sectarian or at least critical of prevalent social trends and the latter is intended to enable organizational decisions to be made sharply and quickly along lines that seem to dispense with social critique.